1986
DOI: 10.1093/oxfordjournals.eurheartj.a061951
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the degree of coronary artery disease and of left ventricular function and the duration of the QT-interval in ECG*

Abstract: Advanced coronary artery disease (CAD), impaired left ventricular function and prolongation of the QT-interval are considered risk factors for sudden cardiac death in CAD-patients. So far, however, there are no studies investigating in detail whether there is a correlation between the QT-interval and changes in coronary anatomy or changes in left ventricular function. Therefore, coronary angiographic data were related to QT-intervals in 304 patients, who were catheterized because of suspected coronary artery d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 0 publications
0
24
0
1
Order By: Relevance
“…These variations may be even greater in patients with cardiovascular disease (15). It has been demonstrated that sympathetic and parasympathetic tone alter the relation between QT interval and heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…These variations may be even greater in patients with cardiovascular disease (15). It has been demonstrated that sympathetic and parasympathetic tone alter the relation between QT interval and heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…QT dispersion (QTD) is defined as the difference between the longest and the shortest QT intervals on surface ECG [6]. An increase in QTD is reported to predict the occurrence of life-threatening ventricular tachyarrhythmias and sudden cardiac death in patients with ischemic heart disease [7]. …”
Section: Introductionmentioning
confidence: 99%
“…13 An increase in QT dispersion is reported to predict the occurrence of life-threatening ventricular tachyarrhythmias and sudden cardiac death in patients with ischemic heart disease. 14 Tikiz, et al had studied the patients with single vessel CAD had wider resting QT dispersion when compared to control group, which further increased significantly with exercise. 15 Stierle, et al shows a relation Between QT dispersion and the Extent of Myocardial Ischemia in Patients with three vessel Coronary Artery disease.…”
mentioning
confidence: 99%